Public Service Transformation (A Case Study of Online Single Submission at The Office of Investment and Integrated Services Magelang Municipality) - Angga Dwi Saputra; Arif Budy Pratama; Eny Boedi Orbawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
This study aims to analyse public service transformation from One Stop Integrated Service (PTSP) to Online Single Submission (OSS) model. The study was conducted at The Office of Investment and Integrated Services (DPMPTSP) Magelang Municipality. Using case study as a research strategy, the data was collected from in-depth interviews and documentation. The data were analysed using taxonomic analysis techniques. The results show some changes in several dimensions of services such as data input, service focus, issuing business licenses process, service systems and the time needed in the licensing service process. From the functional-structural theory perspective, service transformation from PTSP to Online Single Submission at The Office of Investment and Integrated Services Magelang Municipality underwent due to regulations from the central government with the aim of accelerating and facilitating business services. However, the licensing application system integration has not been running well due to application system transition. Thus, the service transformation process from manual to online should pay attention to the integration of the old system into the new one.